Perancangan Mesin Pencetak Kerupuk Cassava dengan Menggunakan Metode Quality Function Deployment (QFD) - Achmad Nur Qhozali; Hery Murnawan (SURYA TEKNIKA, 2024)
UKM Bintang Anugrah is a company that operates in the snack food sector, especially cassava crackers, which produces 150kg to 250kg of cassava every day and produces 600 packs of 250g and 350 packs of 500g. The cracker molding process is still done manually using flower-shaped cake molds, which not only takes a long time, but also produces less than optimal output and takes up to 5 hours. This research aims to design an automatic printing machine to increase production efficiency and reduce operational costs. By using the Quality Function Deployment (QFD) method, the needs of workers and customers are identified, such as increasing production speed, ease of operation and process efficiency. The machine's technical specifications are then adapted to these needs. The designed automatic printing machine is able to speed up the printing process and reduce worker workload, increasing production capacity by up to 40%. With this machine, SME Bintang Anugrah can produce more crackers in a shorter time, which allows the company to better meet market demand and reduce operational costs, thereby increasing competitiveness in the snack food industry.